MSME Empowerment Through Business Coaching Programs and Massive Online Open Course - Herdiana Dyah Susanti; Dian Arief Pradana; Moh. Fahrurrozi; Mahfud (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The impact of the COVID-19 pandemic has hit various sectors, including micro, small and medium enterprises (MSMEs). To stop the spread of this pandemic, many activities have been restricted under massive social restriction programs. Founded in 2015 and focused on empowering his MSMEs in Banyuwangi district and surrounding areas, Banyuwangi Untag Incubitek is committed to helping MSMEs to deal with this disease. Banyuwangi Untag Incubitek plays a role in helping MSMEs by working with mentors, coaches, financial institutions, government agencies and even foundations dedicated to his MSME development. His MSMEs who participate in this program include students, alumni and the general public. Gain the knowledge and skills to build and improve your existing business. The technique used in this empowerment program is to provide online coaching via Zoom platform, Untag Banyuwangi's Learning Management System